2013
DOI: 10.1523/jneurosci.5107-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Cofilin Regulates Extinction of Conditioned Aversive Memory via AMPAR Trafficking

Abstract: Actin dynamics provide an important mechanism for the modification of synaptic plasticity, which is regulated by the actin depolymerizing factor (ADF)/cofilin. However, the role of cofilin regulated actin dynamics in memory extinction process is still unclear. Here, we observed that extinction of conditioned taste aversive (CTA) memory led to temporally enhanced ADF/cofilin activity in the infralimbic cortex (IrL) of the rats. Moreover, temporally elevating ADF/cofilin activity in the IrL could accelerate CTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Indeed, this has been demonstrated in an independent study shortly after: during chemical LTP, cofilin1-dependent synaptic accumulation of the AMPAR subunit GluR1 precedes spine enlargement which, on the other hand, depends on cofilin1 inactivation [22]. A role of cofilin1 in AMPAR accumulation during synaptic plasticity is in very good agreement with the reduced LTP in cofilin1 mutant mice [21], and has been corroborated recently by the finding that manipulation of ADF/cofilin activity in the rat infralimbic cortex altered synaptic accumulation of GluR1 and GluR2 in a bidirectional manner, independently of spine morphological changes [62]. These studies, together with those discussed above (see section: Function of cofilin1 and ADF in structural plasticity), suggest a temporal sequence of ADF/cofilin activation and inactivation during LTP, relevant for initial spine enlargement and synaptic AMPAR accumulation (both dependent on ADF/cofilin activation), followed by consolidation of structural changes (dependent on ADF/cofilin inactivation).…”
Section: Function Of Adf/cofilin In Synaptic Ampa Receptor Accumulationmentioning
confidence: 62%
See 1 more Smart Citation
“…Indeed, this has been demonstrated in an independent study shortly after: during chemical LTP, cofilin1-dependent synaptic accumulation of the AMPAR subunit GluR1 precedes spine enlargement which, on the other hand, depends on cofilin1 inactivation [22]. A role of cofilin1 in AMPAR accumulation during synaptic plasticity is in very good agreement with the reduced LTP in cofilin1 mutant mice [21], and has been corroborated recently by the finding that manipulation of ADF/cofilin activity in the rat infralimbic cortex altered synaptic accumulation of GluR1 and GluR2 in a bidirectional manner, independently of spine morphological changes [62]. These studies, together with those discussed above (see section: Function of cofilin1 and ADF in structural plasticity), suggest a temporal sequence of ADF/cofilin activation and inactivation during LTP, relevant for initial spine enlargement and synaptic AMPAR accumulation (both dependent on ADF/cofilin activation), followed by consolidation of structural changes (dependent on ADF/cofilin inactivation).…”
Section: Function Of Adf/cofilin In Synaptic Ampa Receptor Accumulationmentioning
confidence: 62%
“…Apart from its role in structural plasticity, several recent studies established a novel postsynaptic function for cofilin1 in trafficking and synaptic accumulation of a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPAR) [21,22,62]. Initially, lateral diffusion of the quantum dot-labeled AMPAR subunit GluR2 was shown to be compromised in the extrasynaptic, but not in the synaptic compartment of hippocampal neurons from cofilin1 mutants, and, presumably as a consequence of impaired lateral diffusion, spatial confinement of GluR2 was increased [21].…”
Section: Function Of Adf/cofilin In Synaptic Ampa Receptor Accumulationmentioning
confidence: 99%
“…Therefore, the lack of c-Fos protein induction in IL by retrieval of recent COA memory indicates that c-Fos is not one of the obligatory proteins that have to be newly formed for consolidation of extinction memory. Indeed, other proteins have been identified as being important in IL for consolidation of recent aversion memory extinction like coffilin and BDNF (Wang et al, 2013;Xin et al, 2014). Another possibility that could explain the lack of c-Fos induction in IL by recent COA retrieval could be related to the absence of analyses of subtypes of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that LIMK1 expression was decreased in the inner granule cells beneath the PC. As LIMK1 might be a useful candidate for studying memory (Wang et al, 2013;Wolf et al, 2014), the present results suggest that LIMK1 and AD are connected from the cytoplasm to the nucleus, which might cause several degenerative diseases.…”
Section: Discussionmentioning
confidence: 50%